Complete heart block in patients with peroneal muscular atrophy. Issue 551 (September 1971) - Ponder, B. A. J.; Chatterjee, K.; Sutton, G. C.
Abstract : Two patients with peroneal muscular atrophy who also had complete heart block are reported. The pathogenesis of heart block in one of these patients was investigated by left ventricular volume analysis which showed a normal ejection fraction, indicating intact left ventricular function. This patient in addition had a normal coronary arteriogram. These findings suggest that heart block in patients with peroneal muscular atrophy may be due to primary conduction tissue disease rather than cardiomyopathy.